2021
DOI: 10.1021/jacs.1c03829
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insights into Privileged Stereocontrolling Interactions Involving Chiral Phosphates and Iminium Intermediates

Abstract: The precise design of a catalyst for a given reaction is extremely difficult, often requiring a significant empirical screening campaign to afford products in high yields and enantiomeric excess. Design becomes even more challenging if one requires a catalyst that performs well for a diverse range of substrates. Such "privileged" catalysts exist, but little is known why they operate so generally. We report the results of computations which show that when substrate and catalyst features are conserved between si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…However, recent density functional theory (DFT) calculations have shown these pathways can lead to catalyst deactivation, and this reaction event would also explain the experimental data . In our computational study of the Hantzsch ester hydrogenation of α,β-unsaturated iminiums, we showed that the reaction proceeds via a transition state (TS) involving two hydrogen-bonding (H-bond) contacts with both reactants . Steric interactions between reasonably large groups on the catalyst and substrate in addition to the iminium H-bond control the product outcome (Figure B, Mechanism C).…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…However, recent density functional theory (DFT) calculations have shown these pathways can lead to catalyst deactivation, and this reaction event would also explain the experimental data . In our computational study of the Hantzsch ester hydrogenation of α,β-unsaturated iminiums, we showed that the reaction proceeds via a transition state (TS) involving two hydrogen-bonding (H-bond) contacts with both reactants . Steric interactions between reasonably large groups on the catalyst and substrate in addition to the iminium H-bond control the product outcome (Figure B, Mechanism C).…”
Section: Introductionmentioning
confidence: 62%
“…Further, simple models that can be sketched by hand are qualitative and do not provide a quantitative prediction of the enantioselectivity output . Accordingly, we deployed statistical modeling tools, which could greatly enhance the application and predictive power of our reaction models. To connect these nine disparate reaction types, a comprehensive multivariate linear regression (cMLR) model that relates the features of all of the reaction components to the experimentally obtained enantioselectivity outcomes conveyed as ΔΔ G ‡ would be required (see SI for full details on workflow, statistical models considered, and additional validation tests) . These tools have been used recently in other contexts but often without the guidance of TS calculations, , which are valuable for formalizing mechanistic principles that enable the prediction of product stereochemistry and are required to carefully consider the limits of model generality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in the vast majority of cases, the noncovalent interactions required for enantioinduction 11 are not built into the catalytic system a priori but rather selected during optimization by a lengthy trial-and-error approach and rationalized only a posteriori . 12 Alternatively, the chiral anion can be precisely positioned by a rigid covalent linkage to the ligand, as in the “tethered counterion-directed catalysis” strategy recently disclosed by Marinetti, Guinchard, and co-workers for the enantioselective Au(I)-catalyzed tandem cycloisomerization–nucleophile addition to 2-alkynyl enones. 13 However, despite its elegance, this latter approach becomes akin to using a chiral ligand, so it is devoid of the flexibility and combinatorial potential offered by the original two-component ACDC.…”
Section: Introductionmentioning
confidence: 99%